A continuidade das empresas familiares agropecuárias - Silveira, Maria Eugênia Pereira Saraiva (Universidade do Vale do Rio dos Sinos, 2025)
This research focuses on the continuity of family-owned agricultural businesses, aiming to show how planned succession will ensure the continuity of businesses for future generations, especially given the fact that few family businesses manage to reach the third generation of succession, and the combination of mechanisms and instruments of succession planning can contribute to conferring sustainability on the continuity of these businesses. The research problem focuses on answering how to ensure the continuity of family-owned agricultural businesses? From this, effective instruments and mechanisms are presented to prevent the dismemberment of rural structures built by generations at the time of succession. This is the general objective of the work, and to achieve it, as specific objectives, it is necessary to understand the structure of the contemporary Brazilian family and family-owned agricultural businesses, analyze unplanned succession, understand the instruments of succession planning and mechanisms extracted from the principles of family governance. The methodology used is theoretical, descriptive and exploratory, with the use of technical bibliographic procedures, including a systematic review of the literature, as well as analysis of legislative texts and case law. The research was classified as descriptive research, since its objective was to describe the characteristics of a given population or phenomenon, or to establish variable relationships. The research-as-observer method was also used in order to gain knowledge of the culture of families dedicated to the agricultural sector and how the activity develops in this sector. In the end, it was concluded that traditional succession planning instruments, such as wills, donations and holding companies, by themselves, are not capable of ensuring the continuity of agricultural activities in a harmonious way, and effective mechanisms for this can be found in family governance, professionalization and family protocols. As a practical result of the research, a booklet entitled “The continuity of the family agricultural business” was prepared, which provides information in a simple way to rural landowners with the aim of informing them of the existence of legal succession planning instruments and also mechanisms capable of providing sustainability so that rural property, built by at least one generation, is not dismembered at the time of succession.
Keywords: Continuidade; Empresa familiar; Agropecuária; Continuity; Family business; Agriculture; ACCNPQ::Ciências Sociais Aplicadas::Direito